Development of a tender coconut cutting machine - BHAVYA FRANCIS MEENU P. B SINSHA P. V; Er. George Mathew (Guide) (Tavanur 2014 Department of Food and Agricultural Process Engineering)
Development of a tender coconut cutting machine
Development of a tender coconut cutting machine